In situ Probe Microphone Measurement for Testing the Direct Acoustical Cochlear Stimulator - Stieger, Christof; Alnufaily, Yasser H.; Candreia, Claudia; Caversaccio, Marco D.; Arnold, Andreas M. (Frontiers in Neuroscience, 2017)
Hypothesis: Acoustical measurements can be used for functional control of a direct acoustic cochlear stimulator (DACS) Background: The DACS is a recently released active hearing implant that works on the principle of a conventional piston prosthesis driven by the rod of an electromagnetic actuator. An inherent part of the DACS actuator is a thin titanium diaphragm that allows for movement of the stimulation rod while hermetically sealing the housing. In addition to mechanical stimulation, the actuator emits sound into the mastoid cavity because of the motion of the diaphragm. Methods: We investigated the use of the sound emission of a DACS for intra-operative testing. We measured sound emission in the external auditory canal (PEAC) and velocity of the actuators stimulation rod (Vact) in five implanted ears of whole-head specimens. We tested the influence various positions of the loudspeaker actuator and a probe microphone on PEAC and simulated implant malfunction in one example. Results: Sound emission of the DACS with a signal-to-noise ratio > 10 dB was observed between 0.5 and 5 kHz. Simulated implant misplacement or malfunction could be detected by the absence or shift in the characteristic resonance frequency of the actuator. PEAC changed by less than 6 dB for variations of the microphone and loudspeaker actuator position. Conclusion: Our data support the feasibility of acoustical measurements for in situ testing of the DACS implant in the mastoid cavity as well as for post-operative monitoring of actuator function.